Corporal punishment of children: discipline or abuse?. Issue 1 (1st January 2018) - Bassam, Eid; Marianne, Touma Boulos; Rabbaa, Lydia Khabbaz; Gerbaka, Bernard
ABSTRACT: Introduction : Corporal punishment is a public health problem due to its impact on the physical, psychological, and social interactions of children. Objectives : To determine the knowledge of pediatricians in Lebanon regarding corporal punishment, their preventive, educational, and legal role. Methods : A cross-sectional descriptive study conducted on 153 pediatricians in Lebanon, by a questionnaire distributed at the 12th Annual Congress of the Lebanese Pediatric Society and the North Lebanon Pediatric Society. Results : Less than 50% and less then 60% of pediatricians know the effects of physical punishment on the physical and psychic health of the child, respectively. About 74.2% and 23.2% of pediatricians disagree with Article186 of the Lebanese Criminal Code and Lebanese Law422/02 (Article25), respectively. Only 76.2% of Lebanese pediatricians always advise the abandonment of corporal punishment and 4.7% advise its use for discipline. Conclusion : Pediatricians play a fundamental role in the abolition of corporal punishment, but this cannot be accomplished without improving their skills in this area. They are invited to seek legal reforms in Lebanon to abolish the use of corporal punishment as a means of disciplining children.